Moderation of the Board of Commissioners in Determining Earnings Management - Yuni Inawati; Ernanda Oktaviani (UIN Salatiga, 2021)
The problem of this research is earnings management, namely the actions taken by managers in manipulating the numbers presented in the financial statements. This study aims to analyze the effect of tax planning, profitability, and leverage on earnings management with the frequency of board meetings as a moderation. The study population, namely all manufacturing companies listed on Bursa Efek Indonesia (BEI) exchange in 2017-2019. With the sample of 22 companies. The sample selection method used in this research is the purposive sampling method and the data analysis technique uses panel data regression analysis. The study uses secondary data, namely financial statement data from companies listed on the IDX obtained from the website www.idx.co.id. The results show that partially, tax planning, profitability, and leverage don’t have a significant effect on earnings management. The frequency of board meetings has a positive effect in moderating tax planning and leverage on earnings management. However, the frequency of board meetings has not to effect in moderating profitability on earnings management